2019
DOI: 10.1155/2019/1585014
|View full text |Cite
|
Sign up to set email alerts
|

False-Negative Platelet Factor 4 Antibodies and Serotonin Release Assay and the Utility of Repeat Testing in the Diagnosis of Heparin-Induced Thrombocytopenia and Thrombosis

Abstract: Objective To report a case of false-negative serological tests in the diagnosis of heparin-induced thrombocytopenia (HIT) followed by a brief review of the literature on this topic. Case Presentation A 75-year-old Caucasian female patient was admitted with a traumatic right ankle fracture that required open reduction and internal fixation. Despite postoperative subcutaneous heparin chemoprophylaxis, she developed deep vein thrombosis (DVT) and pulmonary embolism (PE) on day 4 and subsequently started on contin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…86,89 Recently, some false-negative test results have been observed for both PF4 antibodies and functional assays, thus justifying the recommendation to repeat the tests when the clinical suspicion remains very strong. 87,90 Nevertheless, perhaps the biggest problem in the identification of pathological HIT is that of "false-positives" since most antibodies identified by initial immunological testing do not lead to activation of platelets in a functional HIT assay. 69,87 Heparin-Dependent Antibodies Many immunological assays have been developed for identifying heparin-PF4 complexes and/or heparin-platelet antibodies causing HIT.…”
Section: Laboratory Testing For Heparin-induced Thrombocytopeniamentioning
confidence: 99%
“…86,89 Recently, some false-negative test results have been observed for both PF4 antibodies and functional assays, thus justifying the recommendation to repeat the tests when the clinical suspicion remains very strong. 87,90 Nevertheless, perhaps the biggest problem in the identification of pathological HIT is that of "false-positives" since most antibodies identified by initial immunological testing do not lead to activation of platelets in a functional HIT assay. 69,87 Heparin-Dependent Antibodies Many immunological assays have been developed for identifying heparin-PF4 complexes and/or heparin-platelet antibodies causing HIT.…”
Section: Laboratory Testing For Heparin-induced Thrombocytopeniamentioning
confidence: 99%
“…His subsequent tests (ELISA and SRA) were found to be positive. [ 30 ] All these evidences indicate a very significant role of clinical suspicion and repeated scoring by 4Ts test in all patients on heparin.…”
Section: Discussionmentioning
confidence: 97%
“…This can lead to false positive diagnoses in approximately 1 in 5 patients tested with immunoassays alone. With a higher specificity at >95%, the SRA is considered to be the gold standard in diagnosing HIT; however, case reports have found that the SRA may be falsely negative in patients who have received massive transfusions, are on immunosuppression, have low antibody titres early in the disease or have undergone multiple rounds of plasmapheresis 2 12–15. A history of cirrhotic coagulopathy may also skew diagnostic testing for HIT 12.…”
Section: Discussionmentioning
confidence: 99%